2015
DOI: 10.1128/jcm.02116-15
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Three Nucleic Acid-Based Assays for BK Virus Quantification

Abstract: With the growing importance of BK virus (BKV), effective and efficient screening for BKV replication in plasma and urine samples is very important for monitoring renal transplant and hematopoietic stem cell transplant recipients, who are at increased risk of BKV-associated diseases. However, recent assays proposed by many manufacturers have not been tested, and the available tests have not been standardized. The aim of the present study was to evaluate and compare the performances of three commercially availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 20 publications
0
11
0
1
Order By: Relevance
“…The prevalence of an infection depends on the sensitivity and specificity of the assay. The assay we used, Altona Real-star® BK virus assay, was comparable with two other commercial assays and was even more sensitive than the other two assays [3].…”
Section: Discussionmentioning
confidence: 78%
“…The prevalence of an infection depends on the sensitivity and specificity of the assay. The assay we used, Altona Real-star® BK virus assay, was comparable with two other commercial assays and was even more sensitive than the other two assays [3].…”
Section: Discussionmentioning
confidence: 78%
“…BKV subtyping and subgrouping were based on the phylogenetic analysis of fragments within VP1 and large T antigen genes (nucleotides 1564 to 2215 and 3021 to 3715, respectively) as previously described (18). In our study, another genotyping scheme was set up, based on a shorter 100-bp segment from nucleotides 1977 to 2076 within VP1.…”
mentioning
confidence: 99%
“…The factors previously cited to impact BKV NAAT quantification include the nucleic acid extraction method and the design of primers and probes that do not account for variation in BKV genotypes (7)(8)(9). The use of commercially available assays, such as Altona, may yield improved agreement between assays, as demonstrated in a study that found reliable and comparable performances of three commercial real-time BKV PCR assays (21). Thus, the use of commercial assays along with a standard calibrator may resolve many of the issues surrounding the heterogeneity in BKV NAAT results.…”
Section: Discussionmentioning
confidence: 80%